2010
DOI: 10.1161/circulationaha.110.958967
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-328 Contributes to Adverse Electrical Remodeling in Atrial Fibrillation

Abstract: Background-A characteristic of both clinical and experimental atrial fibrillation (AF) is atrial electric remodeling associated with profound reduction of L-type Ca 2ϩ current and shortening of the action potential duration. The possibility that microRNAs (miRNAs) may be involved in this process has not been tested. Accordingly, we assessed the potential role of miRNAs in regulating experimental AF. Methods and Results-The miRNA transcriptome was analyzed by microarray and verified by real-time reversetranscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
327
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 413 publications
(358 citation statements)
references
References 53 publications
10
327
1
9
Order By: Relevance
“…A number of profiling studies suggested potential roles for miRs in AF. For example, miR-328 expression was elevated in human AF patients and in a canine AF model although direct functional analysis of miR-328 awaits further experimentation (35). MiR-21 expression was increased in AF patients, a mouse model of spontaneous AF, and age-induced atrial fibrosis whereas miR-21 knockdown suppressed atrial fibrosis and AF promotion in rats (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…A number of profiling studies suggested potential roles for miRs in AF. For example, miR-328 expression was elevated in human AF patients and in a canine AF model although direct functional analysis of miR-328 awaits further experimentation (35). MiR-21 expression was increased in AF patients, a mouse model of spontaneous AF, and age-induced atrial fibrosis whereas miR-21 knockdown suppressed atrial fibrosis and AF promotion in rats (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore CACNA1C and CACNB1, which encode the cardiac L-type Ca 2+ channel 1c-and 1 subunits, are predicted to be potential targets of miR-328. This hypothesis has been verified using adenovirus infection and a transgenic approach to force the expression of miR-328, resulting in enhanced AF vulnerability, diminished L-type Ca 2+ currents, and shortened atrial APD [29].…”
Section: Effect Of Mirnas On Electrical and Molecular Remodeling In Afmentioning
confidence: 85%
“…Unlike polymorphisms in coding genes, polymorphisms in miRNAs are closely related to various diseases, including tumors, nervous system diseases, and cardiovascular diseases. To date, thousands of miRNA genes have been found in diverse animals, with functions in regulating cell death, cell proliferation, and hematopoiesis, and even in the process of cardiovascular disease [29,30]. Increasing evidence has identified an important role for miRNAs in AF initiation and maintenance.…”
Section: Mirna Biologymentioning
confidence: 99%
“…1). Repressed translation of a 1C (Cav1.2) and b 1 (Cavb1) I Ca,L subunits by enhanced miR-328 is one potential mechanism of reduced I Ca,L in human AF [21]. The KCNQ1 gene encoding the major I Ks channel subunit contains putative binding sites for miR-1, which potentially links reduced miR-1 [13] levels with enhanced I Ks current in AF patients [3].…”
mentioning
confidence: 99%
“…exchanger 1 (NCX1) as a novel target of miR-1 [17], suggesting that deregulated miR-1 may contribute to the higher NCX expression and function in AF patients [14]. However, reduced miR-1 is not a consistent finding in AF, because unaltered [21] and enhanced miR-1 levels [4] have also been reported. The reason for these inconsistent findings in atrial miR levels among studies is not known, but might reflect use of right versus left atrial tissue and differences in age, concomitant diseases and medication in the studied patient populations [5,12,29].…”
mentioning
confidence: 99%